2019
DOI: 10.1093/mnras/stz2005
|View full text |Cite
|
Sign up to set email alerts
|

The Lense–Thirring timing-accretion plane for ULXs

Abstract: Identifying the compact object in ultraluminous X-ray sources (ULXs) has to-date required detection of pulsations or a cyclotron resonance scattering feature (CRSF), indicating a magnetised neutron star. However, pulsations are observed to be transient and it is plausible that accretion onto the neutron star may have suppressed the surface magnetic field such that pulsations and CRSFs will be entirely absent. We may therefore lack direct means to identify neutron star systems whilst we presently lack an effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 107 publications
2
50
0
Order By: Relevance
“…The precession of an accretion disc may be driven by a variety of external torques, including tidal effects, radiation pressure driven instabilities, Lense-Thirring precession, magnetic warping and free-free precession (Fragile et al 2007;Maloney & Begelman 1997;Maloney et al 1998;Pringle 1996;Lei et al 2013). Lense-Thirring (solid-body) precession of the large scale-height disc and wind has recently been proposed as the driving mechanism for the modulations (Middleton et al 2018(Middleton et al , 2019b and is somewhat compelling as it requires a misaligned spin and binary axis, the same requirement for the detection of pulsations (King & Lasota 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The precession of an accretion disc may be driven by a variety of external torques, including tidal effects, radiation pressure driven instabilities, Lense-Thirring precession, magnetic warping and free-free precession (Fragile et al 2007;Maloney & Begelman 1997;Maloney et al 1998;Pringle 1996;Lei et al 2013). Lense-Thirring (solid-body) precession of the large scale-height disc and wind has recently been proposed as the driving mechanism for the modulations (Middleton et al 2018(Middleton et al , 2019b and is somewhat compelling as it requires a misaligned spin and binary axis, the same requirement for the detection of pulsations (King & Lasota 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another source of periodicity can arise due to precession of the accretion funnel along which the FRB is beamed (see Section 2.3, and Figures 1 and 5). If the spin axis of the accreting BH or NS is misaligned with the angular momentum axis of the disk, then the Lens-Thirring (LT) torque applied by the rotating spacetime on the disk may cause the latter to precess (e.g., Middleton et al 2019). Numerical simulations have shown that for thick disks (with vertical aspect ratio h/r  0.05 and low effective α viscosity), the warp propagation timescale is shorter than the differential precession timescale, thereby allowing them to precess as rigid bodies with negligible warping (Fragner & Nelson 2010).…”
Section: Periodicitymentioning
confidence: 99%
“…Middleton et al (2018) suggest that the precession can be explained by the Lense-Thirring effect, a consequence of general relativity whereby a massive spinning object induces a precession of orbiting particles that are displaced vertically from the rotation axis, for example, a large-scale height accretion flow. Indeed, Middleton et al (2019) suggest that these timescale periodicities can be used to determine whether the compact object is a black hole or a NS.…”
Section: A 38 Day Superorbital Flux Modulation From Ulx7mentioning
confidence: 99%